The mortality burden attributable to nontrauma fracture for privately insured adults with epilepsy. (27th February 2020) - Whitney, Daniel G.; Bell, Sarah; McNamara, Nancy A.; Hurvitz, Edward A.
Abstract: Objective: Individuals with epilepsy have poor bone development and preservation throughout the lifespan and are vulnerable to nontrauma fracture (NTFx) and post‐NTFx complications. However, no studies have examined the contribution of NTFx to mortality among adults with epilepsy. The objective was to determine whether NTFx is a risk factor for mortality among adults with epilepsy. Methods: Data from 2011 to 2016 were obtained from Optum Clinformatics Data Mart, a nationwide claims database from a single private payer in the United States. Diagnosis codes were used to identify adults (≥18 years old) with epilepsy, NTFx, and covariates (demographics and pre‐NTFx cardiovascular disease, respiratory disease, diabetes, chronic kidney disease, cancer). Crude mortality rate per 100 person‐years was estimated. Cox regression estimated hazard ratios (HRs) and 95% confidence intervals (CIs) were determined for mortality, comparing epilepsy and NTFx (EP + NTFx; n = 11 471), epilepsy without NTFx (EP without NTFx; n = 50 384), without epilepsy and with NTFx (without EP + NTFx; n = 423 041), and without epilepsy and without NTFx (without EP without NTFx; n = 6.8 million) after adjusting for covariates. Results: The 3‐, 6‐, and 12‐month crude mortality rates were highest among EP + NTFx (12‐month mortality rate = 8.79), followed by without EP + NTFx (12‐month mortality rate = 4.80), EP without NTFx (12‐month mortality rate = 3.06), and without EP without NTFx (12‐month mortality rate = 0.47). After adjustments, the mortality rate was elevated for EP + NTFx for all time points compared to EP without NTFx (eg, 12‐month HR = 1.70, 95% CI = 1.58‐1.85), without EP + NTFx (eg, 12‐month HR = 1.41, 95% CI = 1.32‐1.51), and without EP without NTFx (eg, 12‐month HR = 5.23, 95% CI = 4.88‐5.60). Stratified analyses showed higher adjusted HRs of 12‐month mortality for EP + NTFx for all NTFx sites (ie, vertebral column, hip, extremities), all age categories (young, middle‐aged, older), and for both women and men. Significance: Among adults with epilepsy and compared to adults without epilepsy, NTFx is associated with a higher 12‐month mortality rate. Findings suggest that NTFx may be a robust risk factor for mortality among adults with epilepsy.